Influence of Dietary Mannan-oligosaccharide and ï¡-Tocopherol on Intestinal Microbiology and Histomorphology in Broiler Chickens - Sinha, Pallavi; Kumar, Sanjay; Kumar, Kaushalendra; ., Chandramoni; Sinha, Manju; Kumar, Deepak; Kumari, Rajni; Kumari, Sushma (Indian Journal of Animal Nutrition, 2019)
Day-old Vencobb broiler chicks (240) were randomly assigned to 4 dietary treatment groups having 3 replicates of 20 birds each to study the effect of mannan oligosaccharide (MOS) and Î±-tocopherol on intestinal microbiology and histomorphology. The trial lasted for 7 weeks. The chicks were fed with standard basal diet. The control group T1 was fed a basaldiet. The birds in group T2 were fed control diet as in T1 + Î±-tocopherol @ 400IU per kg of feed; in group T3: control diet as in T1 + mannan-oligosaccharide @ 0.4% and in group T4: control diet as in T1 +Î±-tocopherol @ 400IU per kg feed + mannan-oligosaccharide @ 0.4% in feed, respectively. The results of study revealed that supplementation of MOS and AT in the diet of birds showed significant (P